Combination of diminazene aceturate and resveratrol reduces the toxic effects of chemotherapy in treating Trypanosoma evansi infection. (January 2016) - Baldissera, Matheus; Bottari, Nathieli; Rech, Virginia; Nishihira, Vivian; Oliveira, Camila; Cargnin, Lara; Moresco, Rafael; Thomé, Gustavo; Schetinger, Maria; Morsch, Vera; Monteiro, Silvia; Tonin, Alexandre; et al.
Abstract The aim of this study was to evaluate the effects of resveratrol (RSV) in its free or complexed (cyclodextrin) forms in association with diminazene aceturate (DA), as an attempt to reduce the toxic effects of this standard chemotherapy on renal and hepatic samples of mice experimentally infected withT. evansi. In this sense, this experiment was designed in order to test the ability of RSV, in its free or complexed forms, on reducing the damage on lipid membrane and protein oxidation, effects usually observed by using DA. Both forms of RSV were used at 100 mg kg−1, during seven consecutive days. As a result, it was observed that, on renal and hepatic samples, RSV in its free form, when combined with DA, was able to inhibit the increase of thiobarbituric acid reactive species levels. DA caused a decrease in the hepatic levels of advanced oxidation protein products, suggesting changes in protein synthesis; however, when it was combined with RSV, this deleterious effect was not observed. It demonstrates that RSV was able to provide some grade of protection against protein oxidation. Therefore, RSV may represent an alternative in reducing the toxic effect caused by chemotherapy in treating ofT. evansi infection.